2007
DOI: 10.1101/gr.7020108
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis: Genome sequence analysis of lymphogranuloma venereum isolates

Abstract: Chlamydia trachomatis is the most common cause of sexually transmitted infections in the UK, a statistic that is also reflected globally. There are three biovariants of C. trachomatis: trachoma (serotypes A–C) and two sexually transmitted pathovars; serotypes D–K and lyphogranuloma venereum (LGV). Trachoma isolates and the sexually transmitted serotypes D–K are noninvasive, whereas the LGV strains are invasive, causing a disseminating infection of the local draining lymph nodes. Genome sequences are available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
180
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(196 citation statements)
references
References 51 publications
11
180
0
Order By: Relevance
“…For fractionation by sucrosedensity gradient centrifugation, the membrane pellets were resuspended in a solution containing 25% sucrose, 20 mM Tris-HCl, and 0.5 mM EDTA (pH 7.5). This suspension was layered on top of 30,35,40,45,50, and 55% sucrose layers and centrifuged at 100,000 ϫ g for 6 h at 4°C (53)…”
Section: Vol 190 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…For fractionation by sucrosedensity gradient centrifugation, the membrane pellets were resuspended in a solution containing 25% sucrose, 20 mM Tris-HCl, and 0.5 mM EDTA (pH 7.5). This suspension was layered on top of 30,35,40,45,50, and 55% sucrose layers and centrifuged at 100,000 ϫ g for 6 h at 4°C (53)…”
Section: Vol 190 2008mentioning
confidence: 99%
“…The CPn1031 protein belongs to the basic amino acid/polyamine antiporter family of transporters (APA; TC 2.A.3.2) (21), and it was originally annotated as an arginine/ornithine antiporter based on its similarity to the Pseudomonas aeruginosa ArcD transporter (51). In Chlamydia trachomatis L2 the three orthologous genes are cotranscribed (Derek Fisher, Uniformed Services University of the Health Sciences, unpublished data), although a nonsense mutation in the L2 homolog of CPn1032 suggests this system may not be functional in the invasive lymphogranuloma venerum strains (50). This gene order is conserved in all chlamydial genomes, but no homologs are found in the anciently diverged Candidatus Protochlamydia amoebophila UWE25 (an endosymbiont of Acanthamoeba sp.…”
mentioning
confidence: 99%
“…The C. trachomatis genome is ∼1 Mb in size and encodes ∼1,000 genes (6,7). Genome-wide microarray analyses have revealed that ∼80% of all genes are expressed a few hours after infection through the remaining developmental cycle.…”
mentioning
confidence: 99%
“…The genomic sequences of different ocular, urogenital, and LGV strains exhibit Ͼ98% identity and a high degree of synteny (12,25,29,31,50,53,55,59,60). Therefore, the determinants of the different types of infection (invasive or noninvasive) and tissue tropism (eyes, genitals, and lymph nodes) must rely on the few genes present in some strains but not in others and on nucleotide differences which may lead either to proteins with disease group-specific amino acids or to differential gene expression.…”
mentioning
confidence: 99%
“…Our studies suggest that a subset of Inc proteins quences of the inc, pmp, and housekeeping genes analyzed were from the available genomes of 51 C. trachomatis strains (12,25,29,31,50,53,55,59,60). The strains and corresponding genome accession numbers are listed in Table S1 in the supplemental material.…”
mentioning
confidence: 99%